Voting for Winners and Losers in a Hybrid Regime: How Thailand's 2023 Election Shaped Voter Opinion - Jacob I. Ricks; Allen Hicken (Journal of Current Southeast Asian Affairs)
Research in Western Democracies suggests voting has substantive impacts on how one feels about democracy and state institutions. Voting for winners leads to positive feelings while voting for losers has the opposite effect. How, though, do voters interpret electoral results in a system prone to authoritarian intervention? Thailand's 2023 election offers a unique opportunity to examine how voting in a hybrid regime can impact voter opinion. Using a pre- and postelection survey, we demonstrate that, like elections in democracies, an election in a hybrid regime can have a significant impact on voter opinions. When pro-democracy voters win an election in a hybrid regime, the win does boost some support for state institutions. On the other hand, the losing pro-authoritarian voters turned against democracy and expressed reduced support for some state institutions. By contrast, we see an absence of the winner–loser gap regarding some state institutions designed to support authoritarian rule.